COVID-driven innovation in higher education: analysing the collaboration of leadership and digital technology during the pandemic in UiTM Malaysia and UNNES Indonesia / Suwito Eko Pramono … [et al.] - Pramono, Suwito Eko; Wijaya, Atika; Melati, Inaya Sari; Sahudin, Zahariah; Abdullah, Hasni (Universiti Teknologi MARA, 2021)
This study aims to analyse the way leadership and digital technology usage affect the faculty members’ research performance in surviving higher education sustainability during the COVID-19 pandemic. A breakthrough innovation is needed to design a fast-track online work management system. Hence, it requires a loyal contribution from all the faculty members to support this system. This quantitative study conducted in Malaysia and Indonesia, included 260 faculty members from various fields of studies. Using the online questionnaire, it shows that leadership and technology usage plays an important role to maintain faculty members’ research performance during the pandemic. However, it has a slight difference in result between Malaysia and Indonesia in terms of the portion of leadership and digital technology that affected the research performance. The higher education leaders play a stronger role in affecting Malaysian faculty members’ research performance, while Indonesian faculty members are influenced more by digital technology usage than by their leaders. Each of them has a significant implication in designing the effective institution policies in optimizing faculty members’ research performance.